Dacie and Lewis practical haematology (Edinburgh : Elsevier, 2017)
Comprehensive laboratory manual covering techniques and interpretation in hematology, including blood cell morphology, coagulation, and diagnostic methods.
Includes bibliographical references and index
Keywords: Hematology & Laboratory manuals; Blood & Examination